2010
DOI: 10.7863/jum.2010.29.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Fetal Growth in a Rural Indian Cohort and Comparison With a Western European Population

Abstract: Fetal size was smaller in a rural Indian population than in European and urban Indian populations, even in mid pregnancy. The deficit varied for different fetal measurements; it was greatest for AC and BPD and least for FL and HC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 19 publications
(25 reference statements)
2
40
0
Order By: Relevance
“…The inter-observer variation in the extracted fetal measurements was excellent (0.004–0.04%). Full technical details on the fetal measurements [20] and the placental measurements [21] have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter-observer variation in the extracted fetal measurements was excellent (0.004–0.04%). Full technical details on the fetal measurements [20] and the placental measurements [21] have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Serial fetal ultrasound alongside data from birth should provide a better marker of growth restriction. Fetal growth is characterised by substantial centile crossing in individual growth trajectories suggesting it is a highly adaptive process [13]. Studies to date have tended to examine cross sectional associations at each time of measurement [14] or modeled the trajectory using multilevel methods [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Kinare et al observed that fetal size was smaller in a rural Indian population than in European or urban Indian populations with significant differences in fetal biometric measurements. [16]. As observed by Spencer et al, the smallness of Indian fetuses appeared to be related mainly to a smaller abdominal circumference, showing a normal growth pattern significantly below the median for the European growth charts.…”
Section: Discussionmentioning
confidence: 70%
“…Present findings are similar to those of Helcowitz et al 5 However, Kinare AS et al in their study found fetal size to be smaller in rural Indian population than in urban Indian population. 6 In present study, we tried to evaluate growth of fetus using serial SFH measurements Rate of growth of SFH >2 cm per week was considered normal. The sensitivity of diagnosis of IUGR using SFH measurement in our study was found to be 71%, specificity 43%, NPV 33%, PPV of 79% (Table 3, 7).…”
Section: Discussionmentioning
confidence: 99%